Myxosporidies (Myxozoa, Myxosporea) des genres Sphaeromyxa Thélohan, 1892, Myxidium Bütschli, 1882, Zschokkella Auerbach, 1910, Bipteria Kovaljova, Zubtchenko and Krasin, 1983 et Leptotheca Thélohan, 1895 parasites des poissons des côtes sénégalaises (Afrique de l'Ouest) - Kpatcha, T. K.; Diebakate, C.; Toguebaye, B. S. (Journal for African Zoology, 1996)
Examinations of 1630 fish belonging to 37 families and 51 genera caught off Senegal (West Africa) revealed the presence of 9 myxosporidian species. These species were : Sphaeromyxa balbiani Thélohan, 1892 ; Myxidium giganteum Doflein, 1898 ; Myxidium abudefdufi n. sp. ; Myxidium elopsi n. sp. ; Zschokkella mugilidae n. sp. ; Bipteria admisanda Kovaljova, Zubtchenko & Krasin, 1983 ; Leptotheca pegusae n. sp. ; Leptotheca elongata Thélohan, 1895 and Leptotheca lutjani n. sp. They were found in new hosts.